A CRITICAL PERSPECTIVE FOR ALTERNATIVE HUMAN SCIENTISM: APPLICABILITY, DEMYSTIFICATION, AND ADVOCACY - Syed Farid Alatas (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
This paper delves into the intricacies of crafting relevant knowledge across various fields of study, emphasizing the avoidance of ethnocentrism, the liberation of thought, and the impactful advocacy towards the discussed subjects. By theorizing the notion of relevance and establishing sociological criteria, the paper introduces the problem of knowledge relevance and proposes a typology of irrelevance, including conceptual, value, mimetic, and topical categories. Conceptual irrelevance is dissected further into the inapplicability of theories and concepts, alongside their sophistry, perversion, and mystification, which render them irrelevant by obscuring reality with flawed reasoning. Through examples, the paper illustrates both irrelevant and relevant bodies of knowledge, using the study of religion and the critique of Islamic economics as cases of conceptual irrelevance and relevance, respectively. Additionally, it explores value irrelevance through the lens of disconnected knowledge from its political, economic, and cultural contexts, offering a discourse on sectarian persecution, specifically the persecution of Shi’ites in Malaysia, as an instance of value relevance. This exploration underscores the paper’s commitment to establishing knowledge that is free from ethnocentrism, intellectually demystifying, and beneficially impactful.